Evaluación de la concentración de Material Particulado pm2,5 y pm1o en la Parroquia de Mulaló, de la Provincia de Cotopaxi en el periodo 2019-2020”. - Lema Basantes, Roberth Santiago (2020)
The purpose of this research was to determine the concentration of PM10 and PM2.5 particulate material generated by the block companies and vehicles in the Mulaló Parish, the investigation was planned in 4 objetives; characterize the study area, monitor the concentracion of PM10 y PM2.5, compare the database with the TULSMA Ecuadorian Regulations, Book VI Annex 4 and propose mitigation strategies. Therefore, the study area was characterized where two strategic points were identified to carry out the monitoring, the monitoring was carried out according to EPA-450 / 4-87-007, once the respective monitoring was performed, the database where the TULSMA Ecuadorian book VI Annex 4 was compared, indicating that for PM10 it is 100 µg/m3 and for PM2.5 it is 50 µg/m3. The data obtained in the monitoring were within the permissible limits, although at certain times there were high concentrations as in the first monitoring point in the Barrio San Ramón 0.045 µg/m3 of PM10 was obtained during the hours of 11 am and 0.042 µg/m3, of PM2.5 in the 15 pm schedule, at the second monitoring point in the Mulaló Parish Center the following values were obtained 0.039 µg/m3 of PM10 in the schedule of 18 pm and 0.147 µg/m3 of PM2.5 at 18 pm, concluding that the highest concentration of particulate material occurs in the Mulaló Parish vehicular traffic, based on the data obtained, proposals for mitigation.